Reliability and validity of the Chinese version of the Childhood Trauma Questionnaire-Short Form for inpatients with schizophrenia. - Wen-Juan Jiang; Bao-Liang Zhong; Lian-Zhong Liu; Yong-Jie Zhou; Xiao-Hua Hu; Yi Li (PLoS ONE, 2018)
BACKGROUND:The evaluation of childhood trauma is essential for the treatment of schizophrenia. The short form of Childhood Trauma Questionnaire (CTQ-SF) is a widely used measure of the experience of childhood trauma in the general population. Nevertheless, data regarding the psychometric property of CTQ-SF for assessing childhood trauma of patients with schizophrenia are very limited. METHODS:Two hundred Chinese inpatients with schizophrenia completed the Chinese CTQ-SF, the Child Psychological Maltreatment Scale (CPMS), the Impact of Events Scale-Revised (IES-R), and the Dissociative Experiences Scale-II (DES-II). To assess test-retest reliability of the CTQ-SF, all patients completed the CTQ-SF again two weeks later. Concurrent and convergent validity was assessed by analyzing Pearson bivariate correlation coefficients between CTQ-SF and CPMS, IES-R, and DES-II. RESULTS:The Cronbach's α coefficient of the Chinese CTQ-SF was 0.81, and the two-week re-test reliability was 0.81 (P<0.01). The criterion-related validity coefficients of CTQ-SF with the CMPS, IES-R and DES-II were 0.61, 0.41, and 0.51, respectively. CONCLUSION:The Chinese CTQ-SF has satisfactory psychometric properties to measure childhood abuse or neglect in Chinese inpatients with schizophrenia.